2008
DOI: 10.17305/bjbms.2008.2892
|View full text |Cite
|
Sign up to set email alerts
|

Spirulina Platensis Protects Against Renal Injury in Rats with Gentamicin-Induced Acute Tubular Necrosis

Abstract: The present study was carried out to evaluate the renoprotective antioxidant effect of Spirulina platensis on gentamicin-induced acute tubular necrosis in rats. Albino-Wistar rats, (9male and 9 female), weighing approximately 250 g, were used for this study. Rats were randomly assigned to three equal groups. Control group received 0,9 % sodium chloride intraperitoneally for 7 days at the same volume as gentamicin group. Gentamicin group was treated intraperitoneally with gentamicin, 80 mg/kg daily for 7 days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Similar findings were reported by Avdagic et al. [33] using similar doses of S. platensis and GM, except that the treatment was carried out for 9 days. The three papers suggested that the basis of the nephroprotective action of Spirulina was its antioxidant activity against the generation of free radicals induced by GM.…”
Section: Agents That Either Ameliorate or Prevent Gm Nephrotoxicitysupporting
confidence: 89%
“…Similar findings were reported by Avdagic et al. [33] using similar doses of S. platensis and GM, except that the treatment was carried out for 9 days. The three papers suggested that the basis of the nephroprotective action of Spirulina was its antioxidant activity against the generation of free radicals induced by GM.…”
Section: Agents That Either Ameliorate or Prevent Gm Nephrotoxicitysupporting
confidence: 89%
“…Many previous literatures showed the hepatoprotective effects of SP and its active constituents against drugs, chemicals and xenobiotics [24], [55][56]. The nephroprotective effects of SP have been reported against renal injury induced by gentamicin [27], [57] as well as oxalate [58][59]. Moreover, the antioxidant effects of SP have been reported against sodium fluoride-induced oxidative alterations in offspring of pregnant rats [60].…”
Section: Discussionmentioning
confidence: 97%
“…S. platensis was proved to have normalized the histopathological changes caused by dibutyl nitrosamine-induced rats (Ismail, 2009). S. platensis was proved to have minimized the kidney injury caused in gentamicin-and nitrate-induced rats at the dosage 1000 mg kg À1 (Avdagić et al, 2008).…”
Section: Studies On Spirulina Platensismentioning
confidence: 99%
“…S. fusiformis was reported to treat renal toxicity against cisplatininduced toxicity in rats at the dosage 500 mg kg À1 (Avdagić et al, 2008). S. fusiformis was reported to protect against genotoxicity caused by cisplatin-and urethane-induced toxic mice at the dosage 250 mg kg À1 (Rasool et al, 2006).…”
Section: Studies On Spirulina Fusiformismentioning
confidence: 99%